2005
DOI: 10.1021/bi048089z
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation Mechanism of the Aspartate Receptor:  Electrostatics of the Adaptation Subdomain Play a Key Role in Modulating Kinase Activity

Abstract: The aspartate receptor of the Escherichia coli and Salmonella typhimurium chemotaxis pathway generates a transmembrane signal that regulates the activity of the cytoplasmic kinase CheA. Previous studies have identified a region of the cytoplasmic domain that is critical to receptor adaptation and kinase regulation. This region, termed the adaptation subdomain, contains a high density of acidic residues, including specific glutamate residues that serve as receptor adaptation sites. However, the mechanism of sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
105
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(113 citation statements)
references
References 44 publications
8
105
0
Order By: Relevance
“…A recent study showed that electrostatic repulsion between negative charges on the surface of the subdomain modulates the packing between the adjacent helices of the two subunits within the homodimer, thereby regulating kinase activity (69). Covalent modification of the receptor adaptation sites is believed to modulate this electrostatic interaction in the same way, because methylation or amidation of the adaptation sites decreases the electrostatic repulsion between subunits, thereby stabilizing the helix interactions and activating the kinase.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that electrostatic repulsion between negative charges on the surface of the subdomain modulates the packing between the adjacent helices of the two subunits within the homodimer, thereby regulating kinase activity (69). Covalent modification of the receptor adaptation sites is believed to modulate this electrostatic interaction in the same way, because methylation or amidation of the adaptation sites decreases the electrostatic repulsion between subunits, thereby stabilizing the helix interactions and activating the kinase.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the adaptation region is highly anionic and is regulated by an electrostatic mechanism involving the adaptation site glutamates and several other anionic side-chains lining the subunit-subunit interface [58]. Covalent neutralization of an interfacial anion by methyl esterification or amidation stabilizes the interface and activates kinase, whereas simultaneous neutralization of all anions locks the receptor in the kinaseactivating state [58] Conformational signaling in the protein interaction region, where the kinase interacts, remains poorly understood. However, like the adaptation region, its subunit interface seems to be crucial for signal transmission because many 'lock-on' mutations occur at interfacial locations [54,59].…”
Section: Signaling In the Kinase Control Modulementioning
confidence: 99%
“…The other is tilting of dimers relative to the central trimer axis, detected by changes in dimer-to-dimer FRET [47,48]. In principle, such macroscopic transitions could be driven by changes in supercoiling, or supercoiling-dependent flexibility of the four-helix bundle of the kinase control module [46,58]. By triggering changes in inter-dimer distances or contacts, macroscopic transitions could have an important role in the strong positive signaling cooperativity between dimers, within or between trimers.…”
Section: Macroscopic Transitions In the Trimer-of-dimersmentioning
confidence: 99%
See 2 more Smart Citations